Empowering Esrd Patients For Assisted Self Nutritional Care: A Simple But Effective Intervention For Improving Nutritional Status Of Hemodialysis Patients - Pratim Sengupta; Sumanta Biswas; Rumpa Nandy; AR Nandy (The Korean Society of Nephrology, 2012)
Protein energy wasting (PEW) is a prevalent problem among hemodialysis patients. Lack of adherence to dietary principle based conventional diet charts often fail to satisfy the nutritional requirements of the patients. We studied the effect of simple nutritional training and empowerment of the patients to formulate their own dietary menu in nutritional parameters of hemodialysis patients in 68 stable non diabetic End stage renal disease (ESRD) patients who are on maintenance hemodialysis. The factors which otherwise can affect the nutritional status like sepsis, malignancy,tuberculosis were excluded. At the beginning patient's baseline nutritional status was assessed by anthropometric measurements, Subjective Global Assessment and serum albumin level. Body composition was assessed by linear regression equation (Durin-Womersley) and Siri equation. The patients were divided in two comparable groups (Group-A&B). In group A patients were prescribed individualized dietary prescription; based on their nutritional allowance as per KDOQI guideline. In Group-B the patients were initially made familiar with the dietary principals of the commonly consumed food. Then they were trained by renal nutritionist by study material, visual aid, and proportional food models and one to one discussion to formulate a dietary menu, by these they were empowered to formulate their own dietary menu. They were constantly assisted when faced any problem. In both the group the nutritional parameters were reassessed after three months of intervention. The results were analyzed statistically. There was statistically significant mean increment in the fat free mass index in GroupB[0.8%(Gr.-A)Vs1.0%(Gr.-B),(p<0.05)], the mean increment in the serum albumin in the GroupB was also significantly higher than GroupA[(0.6gm/dl(Gr.A) Vs 0.9 gm/dl(Gr.B), p<0.0]).Compared to Group-A there was statistically favorable anthropometric changes in Group-B. In conclusion patient empowerment and self nutrition care is proved to be an effective intervention for improving nutritional status in hemodialysis patients.